Maxillary Molar Root Displacement Into The Maxillary Sinus - John Chong Keat Hon; Azrul Hafiz (USIM Press, 2024)
MJoSHT 2021, Volume 7, Special Issue on Clinical Scenarios In Medicine, A Malaysian Experience. eISSN: 2601-0003